2023
DOI: 10.3390/molecules28062640
|View full text |Cite
|
Sign up to set email alerts
|

Production of Tetramethylpyrazine from Cane Molasses by Bacillus sp. TTMP20

Abstract: 2,3,5,6-Tetramethylpyrazine (TTMP) is an active ingredient of Ligusticum wallichii Franch. It can be used in medicine and food fields. In this study, Bacillus sp. TTMP20 was applied to produce TTMP using cane molasses as a carbon source. After pretreatment with phosphoric acid, 170 mL/L treated molasses, combined with 10 g/L yeast powder, 30 g/L tryptone and 30 g/L (NH4)2HPO4 were used for fermentation. After 36 h, TTMP output reached the highest value of 208.8 mg/L. The yield of TTMP using phosphoric acid-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In our previous study published in Molecules , the production of TTMP using molasses instead of glucose achieved good results, but the maximum TTMP yield did not exceed 1000 mg/L [ 27 ]. In this study, the use of molasses instead of glucose as the carbon source and soybean meal instead of tryptone as the nitrogen source resulted in a maximum yield of TTMP that reached 1328.95 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study published in Molecules , the production of TTMP using molasses instead of glucose achieved good results, but the maximum TTMP yield did not exceed 1000 mg/L [ 27 ]. In this study, the use of molasses instead of glucose as the carbon source and soybean meal instead of tryptone as the nitrogen source resulted in a maximum yield of TTMP that reached 1328.95 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the ability of a cheap carbon source (molasses) to produce TTMP was investigated [ 27 ]. The highest TTMP yield (895.13 mg/L) was obtained after 36 h of fermentation with molasses as the carbon source and tryptone as the organic nitrogen source.…”
Section: Introductionmentioning
confidence: 99%
“…42 Our studies have shown that strain DW6 had a broad spectrum of carbons including monosaccharide and disaccharide, and nitrogen sources including organic and inorganic ones, indicating that the waste sugarcane molasses can be used as both carbon and nitrogen substrates. 43 Therefore, batch fermentation using sugarcane molasses as substrates without the supplementation of nitrogen sources by strain DW6 was first carried out in shaking flasks. As shown in Fig.…”
Section: Fed-batch Fermentation Of Sugarcane Molasses As Substrates F...mentioning
confidence: 99%